ORACLE: An analytical approach for T1, T2, proton density, and off‐resonance mapping with phase‐cycled balanced steady‐state free precession - Plähn, Nils M. J.; Safarkhanlo, Yasaman; Açikgöz, Berk C.; Mackowiak, Adèle L. C.; Radojewski, Piotr; Bonanno, Gabriele; Peper, Eva S.; Heule, Rahel; Bastiaansen, Jessica A. M. (Magnetic resonance in medicine, 2025)
Purpose To develop and validate a novel analytical approach simplifying T1$$ T_1 $$, T2$$ T_2 $$, proton density (PD), and off‐resonance Δf$$ Δ f $$ quantifications from phase‐cycled balanced steady‐state free precession (bSSFP) data. Additionally, to introduce a method to correct aliasing effects in undersampled bSSFP profiles. Theory and Methods Off‐resonant‐encoded analytical parameter quantification using complex linearized equations (ORACLE) provides analytical solutions for bSSFP profiles. which instantaneously quantify T1$$ T_1 $$, T2$$ T_2 $$, proton density (PD), and Δf$$ Δ f $$. An aliasing correction formalism was derived to allow undersampling of bSSFP profiles. ORACLE was used to quantify T1$$ T_1 $$, T2$$ T_2 $$, PD, T1$$ T_1 $$/T2$$ T_2 $$, and Δf$$ Δ f $$ based on fully sampled (N=20$$ N=20 $$) bSSFP profiles from numerical simulations and 3T MRI experiments in phantom and 10 healthy subjects' brains. Obtained values were compared with reference scans in the same scan session. Aliasing correction was validated in subsampled (N=4$$ N=4 $$) bSSFP profiles in numerical simulations and human brains. Results ORACLE quantifications agreed well with input values from simulations and phantom reference values (R2 = 0.99). In human brains, T1$$ T_1 $$ and T2$$ T_2 $$ quantifications when compared with reference methods showed coefficients of variation below 2.9% and 3.9%, biases of 182 and 16.6 ms, and mean white‐matter values of 642 and 51 ms using ORACLE. The Δf$$ Δ f $$ quantification differed less than 3 Hz between both methods. PD and T1$$ T_1 $$ maps had comparable histograms. The Λ$$ \varLambda $$ maps effectively identified cerebrospinal fluid. Aliasing correction removed aliasing‐related quantification errors in undersampled bSSFP profiles, significantly reducing scan time. Conclusion ORACLE enables simplified and rapid quantification of T1$$ T_1 $$, T2$$ T_2 $$, PD, and Δf$$ Δ f $$ from phase‐cycled bSSFP profiles, reducing acquisition time and eliminating biomarker maps' coregistration issues.